Exploring the Role of Project-Based Learning in Promoting HOTS : An EFL Classroom’s Voice - Raudhah Diara Putri; Sri Setyarini (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Indonesian EFL senior high school students. Traditional EFL instruction often emphasizes lower-order cognitive skills, limiting students' ability to analyze, evaluate, and create in English. This research explored student experiences with PBL and its impact on HOTS development. Semi-structured interviews were conducted with five 11th-grade students participating in environmental-themed PBL activities. Thematic analysis identified patterns in student experiences and perceptions. Findings reveal that students perceive PBL as significantly more engaging than traditional instruction, fostering enhanced motivation, deeper understanding, and collaborative competencies. Students demonstrated active engagement in higher-order cognitive processes through research activities, critical discussions, and creative project development. Collaborative dimensions particularly enhanced analytical and evaluative thinking as students examined diverse perspectives. Implementation challenges emerged, including time management difficulties, group dynamics issues, resource limitations, and presentation anxiety. These challenges highlight PBL's complexity and the need for comprehensive support systems. The study concludes that while PBL effectively promotes HOTS development in EFL contexts, successful implementation requires systematic support, including project management instruction, collaborative skills development, adequate technological resources, and continuous professional development for educators.